Determinants of Quality of Life Among Hypertensive Patients - Sya'id, Achmad; Tursina, Hella Meldy (Journal of Nursing Science Update (JNSU), 2025)
Hypertension significantly affects patients' quality of life; however, awareness of its contributing factors remains inadequate. This study elucidates the determinants influencing the quality of life among patients with hypertension. A cross-sectional observational study was conducted involving 100 hypertension patients at the Patrang Jember Health Centre, utilizing quota sampling. The quality of life was assessed using the EuroQol five-dimensional three-level (EQ-5D-3L) instrument. Relationships between demographic variables and quality of life were analysed using chi-square tests, with statistical significance established at p<0.05. Among the participants, 67% reported experiencing a poor quality of life. The majority of subjects were aged 50 to 70 years (58%), male (51%), employed (70%), possessed a higher level of education (54%), had health insurance (63%), and reported no complications (73%). Statistical analysis revealed significant associations between quality of life and the presence of complications (p=0.000), employment status (p=0.001), educational attainment (p=0.000), and health insurance coverage (p=0.000). No significant relationships were identified with age (p=0.059) or gender (p=0.388). In conclusion, the presence of complications, employment status, educational attainment, and health insurance coverage significantly influence the quality of life in patients with hypertension. These findings underscore the need to develop targeted interventions that address modifiable factors to enhance patient outcomes and overall well-being.